ASSESSING THE RELIABILITY OF CLINICAL NODAL STAGING IN ORAL SQUAMOUS CELL CARCINOMA: CORRELATION WITH HISTOPATHOLOGICAL FINDINGS (Bangladesh Journal of Medical Science, 2026)
Introduction The most significant prognostic factor in oral squamous cell carcinoma (OSCC) is the presence of cervical lymph node metastases. Extranodal extension (ENE) approximately halves survival rates. Previous studies have demonstrated discordance between clinical and pathological lymph node staging, which has important implications for treatment planning. Objective To evaluate the concordance between clinical (cN) and pathological (pN) lymph node staging and determine the frequency of extranodal extension (ENE) in patients with OSCC. Secondary objectives included describing the frequency distribution of age, sex, smoking habits, anatomical location, and histological subtypes of OSCC in a Bangladeshi population. Methods A retrospective analysis was conducted on 95 consecutive cases of OSCC treated with primary tumor resection and neck dissection. The 8th edition of the AJCC/UICC TNM staging system was used to evaluate clinical (cN) and pathological (pN) nodal staging. The prevalence of ENE was assessed in all OSCC patients and in the clinically node-negative (cN0) subgroup. Sociodemographic and tumor-related variables were also recorded. Results Concordance between cN and pN was observed in 51.6% of patients (n = 49/95). Pathological upstaging occurred in 26.3% (n = 25/95) and pathological downstaging in 22.1% (n = 21/95) of cases. ENE was identified in 23 patients (24.2%). The study sample comprised 60% males and 40% females, with a mean age at diagnosis of 60.3 years (range: 25–85 years). A positive smoking history was reported in 76.3% of patients. The most common anatomical sub-sites were the tongue (43.2%) and the floor of the mouth (34.1%). The majority of tumors (62.1%) were conventional, moderately to poorly differentiated squamous cell carcinomas. Conclusion There is moderate concordance between clinical and pathological nodal staging when the 8th edition TNM system is applied. ENE is present in a significant proportion of OSCC patients at the time of diagnosis, including those with clinically node-negative necks. These findings underscore the importance of comprehensive pathological assessment for accurate staging and treatment planning.Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S336-S344